The situation room the inside story of presidents in crisis - Stephanopoulos, George 1961- (Grand Central, 2024)
"George Stephanopoulos, former senior advisor to President Clinton and for more than 20 years host of This Week and Good Morning America, recounts never-before-told crises that decided the course of history, from the place 12 presidents made their highest-pressure decisions: the White House Situation Room. No room better defines American power and its role in the world than the White House Situation Room. And yet, none is more shrouded in secrecy and mystery. Created under President Kennedy, the Sit Room has been the epicenter of crisis management for presidents for more than six decades. Time and again, the decisions made within the Sit Room complex affect the lives of every person on this planet. Detailing close calls made and disasters narrowly averted, THE SITUATION ROOM will take readers through dramatic turning points in a dozen presidential administrations, including: Incredible minute-by-minute transcripts from the Sit Room after both Presidents Kennedy and Reagan were shot; The shocking moment when Henry Kissinger raised the military alert level to DEFCON III while President Nixon was drunk in the White House residence; The extraordinary scene when President Carter asked for help from secret government psychics to rescue American hostages in Iran; A vivid retelling of the harrowing hours during the 9/11 attack; New details from Obama administration officials leading up to the raid on Osama Bin Laden; And a first-ever account of January 6th from the staff inside the Sit Room. THE SITUATION ROOM is the definitive, past-the-security-clearance look at the room where it happened, and the people--the famous and those you've never heard of--who have made history within its walls."
Includes bibliographical references and index.
Keywords: Geschichte; Politik; Lagezentrum; Weißes Haus -- Washington, DC